Recent Advances in Cationic Nanoemulsions for Drug Delivery: Preparation, Properties, and Applications - He, Huanfan; Li, Jiayu; Meng, Hong; He, Yifan; Pei, Xiaojing; Zhang, Ze (Current Pharmaceutical Design, 2025)
Nanoemulsions have gained popularity as drug delivery vehicles owing to the enhanced solubility of insoluble drugs, the augmented stability of photo- and thermosensitive substances, and the facilitation of transdermal permeation of efficacy substances. As the cell surfaces of the skin, cornea, gastrointestinal mucosa, and other cells in living organisms carry negative charges, cationic nanoemulsions (CNE) mainly promote drug absorption through electrostatic effects. In this review, a brief characterization of CNEs is provided, and the types of cationic agents and their roles in nanoemulsions, including cationic surfactants, cationic lipids, cationic polymers, cationized polysaccharides, and phytosphingosine (PS), are discussed. In addition, the current application circumstances of CNEs in ocular drug delivery, mucosal drug delivery, and transdermal drug delivery systems are elaborated on, and the crucial matters that require attention during the research process are briefly discussed. Eventually, the extensive application prospects of CNEs are envisioned.
Keywords: polyelectrolytes